Indonesian EFL Learners’ Critical Thinking in Reading: Bridging the Gap between Declarative, Procedural and Conditional Knowledge - Concilianus Laos Mbato (Humaniora, 2019)
Critical thinking is explicitly mentioned in many school and university curricula around the world including in the Indonesian education curriculum but it is rarely promoted inside the classrooms. Lack of agreement on its definition and clarity of instruction in the curriculum, the unfavourable culture and the teacher-centered teaching arguably prevent critical thinking to grow. Therefore, more research needs to be undertaken on students’ understanding of and engagement in critical thinking in reading. To fll the gap, this study was conducted, which aimed to investigate Indonesian learners’ critical thinking in reading. One research question was postulated, i.e., How critical are Indonesian EFL learners’ thinking in reading? To answer the question, a mixed method approach was undertaken. The participants of this study were 55 semesters four students enrolled in two classes of Critical Reading and Writing II (CRW2) of the English Education Study Program, Sanata Dharma University, Yogyakarta in the even semester of 2014. The instruments employed were a Likert-scale questionnaire and students’ reﬂections. Results from both quantitative and qualitative data analyses suggest that most of the students had sufficient declarative knowledge of critical thinking in reading. However, their procedural and conditional knowledge about critical thinking in reading were insufficient. Overall, students indicated some level of critical thinking in reading, but to become critical, they need to be in a learning environment where their critical thinking in reading could be regularly and intensively nurtured. The findings of the research are expected to inform English teachers, lecturers and researchers in Indonesia and other parts of the world about the importance of designing and carrying out the teaching-learning processes that can enhance learners’ declarative, procedural and conditional knowledge about critical thinking in reading.